'The path you will choose won't be a fairy tale': urban prefiguration and mountain Nostalgia in India's Northwest Himalayas. Issue 1 (2nd January 2020) - Gergan, Mabel; Smith, Sara
ABSTRACT: Overlaid on a collage of street scenes, college students wrote: 'Dear rest of India: Just so you know, I am a proud Indian no matter what my language is, how I look, what I wear, and where I am from'. Development narratives encourage parents to send young people from the Himalayas to major Indian cities for education. Students engage in political actions and play with their identity; simultaneously, racialized as 'foreign', they work out their relationship to the nation through reconsideration of home and city. Based on qualitative research, this article seeks to understand how temporary urban migration shapes students' politics.